Physiochemical Changes in Physical Activity in the Immune System to Prevent Corona Virus in Football Players - Raheem Abd Alwihed; Muzaffar Oraibi Baiji; Hamad Lahmood Taherh; Imad Kadem Yasser (Institute of Medico-legal Publications Pvt Ltd, 2021)
The practice of physical activity is of multiple benefits, including strengthening the immune system byincreasing the effectiveness of the blood circulation that contributes to chemical and physical changesin many of the body’s systems, including the immune system and through physical activity, the bodyneeds greater quantities than normal to bridge the deficiency in which it is active. Minor and major bloodcirculation, as well as an increase in horizontal and vertical breathing processes, as well as an increase in theoxidized blood pressure to meet the need of working muscles, and therefore there is a clear change in thespeed of improvement of the immune system from foreign bodies and the speed of disposal in proportion tothe type and size of For the UFOs, the Corona virus is one of the most dangerous foreign bodies that causeharm or death to humans. The practice of physical activity for a period of (20-30) minutes daily contributesto improving the immune system and helps prevent this virus and other foreign bodies.